Pengetahuan Masyarakat Tentang Antibiotik dan Faktor Sosiodemografi di Indonesia: Implikasi Terhadap Swamedikasi dan Resistensi Antimikroba - Lauale, Evangelina Natali Theresya; Kusuma, Ikhwan Yuda; Mailatunnazza, Nova; Veronica, Laila; Putri, Melisa Mareta; Hilmi, Nahla Habibah; Amalia, Najwa Nurul; Izati, Fina Karunia (Universitas Harapan Bangsa, 2025)
Antibiotics are essential drugs for treating infectious diseases; however, limited public knowledge regarding their proper use contributes to self-medication practices and accelerates antimicrobial resistance. This study aimed to assess the level of antibiotic knowledge among the Indonesian population and analyze its association with sociodemographic factors. A cross-sectional survey was conducted using an online questionnaire distributed through social media, involving 487 respondents from various regions of Indonesia. Data were analyzed using Chi-square tests with SPSS version 27. The results revealed that 63.45% of respondents had high knowledge of antibiotics, 24.85% had moderate knowledge, and 11.70% had low knowledge. Female participants were more likely to demonstrate higher knowledge compared with males (OR = 2.009; 95% CI: 1.336–3.021; p < 0.001), while respondents with a bachelor’s degree showed greater knowledge than those with lower education levels. Occupational and regional differences were observed but were not statistically significant. These findings indicate that although the majority of respondents possessed a good understanding of antibiotics, a considerable proportion still demonstrated poor knowledge, potentially increasing the risk of irrational use. Targeted educational interventions and stricter regulation of antibiotic distribution are essential strategies to enhance public literacy and reduce the threat of antimicrobial resistance in Indonesia.